Safety evaluation of aqueous extracts from Aegle marmelos and Stevia rebaudiana on reproduction of female rats. - Kanokporn Saenphet (2018)
The purpose of this study was to evaluate the safety of a Thai medicinal plant, Aegle marmelos, and a non-caloric sweetener, Stevia rebaudiana, on the reproduction of female rats. Female rats were treated orally with aqueous extract of A. marmelos (6%) and S. rebaudiana at various concentrations (0, 0.2, 1, or 10%) for 60 days (1 ml/day) before mating. The control rats received only distilled water. At the end of the treatment period, treated females were mated with untreated males and the effects on reproduction were examined at day 14 of pregnancy. No notable abnormalities were observed in any of the pregnant rats. The number of corpus lutea, implanted and dead fetuses, as well as the sizes of the fetuses in the treated rats were not significantly different from those of the controls. Based on these results, it may be concluded that aqueous extracts of A. marmelos and S. rebaudiana at the concentrations used in this study do not alter the reproduction of female rats.